Stochastic Dominance and Portfolio Selection of Quoted Nigerian Conglomerates: A Behavioural Finance Approach - Oghenero Godday Oboro, Ph.D1, Enaikpobomene Mina Irejeh, Ph.D.2, Solomon Onyeogo (International Journal of Academic Accounting, Finance & Management Research, 2024)
This paper examined the relevance of stochastic dominance to the selection of six conglomerates’ portfolios from 2012 to 2021. The study extended the Markowitz mean-variance (MMV) approach. The estimation technique considered is 1st, 2nd, and 3rd order stochastic dominance. The study evidenced that two conglomerate stocks were first-order dominant, while four were secondorder dominant and five were third-order dominant. The study concludes that, while stochastic dominance-STOD is useful for determining asset dominance, it does not accurately represent investors' risk preference behavior, unlike the MMV approach. Hence, investors should consider both stochastic dominance approaches. This study was able to contribute to the existing knowledge as it conducted an empirical investigation on the relevance of stochastic dominance techniques on portfolio selection in the Nigerian context, thereby increasing investors’ knowledge on the subject matter. Unlike previous studies, the current study was able to state how different types of investors can harmonize the assertions of both stochastic dominance techniques with those of the stochastic dominance technique on portfolio selection.
Keywords: Stochastic Dominance; Portfolio Selection; Nigerian Exchange Group